The Effectiveness of Mindfulness Training on Self-regulation and Perceived Academic Control of Girl Students - Fatemeh Darabi (Randwick International of Social Science Journal, 2021)
The aim of this study was to determine the effectiveness of mindfulness training on self-regulation and perceived academic control of female students. The research is applied in terms of purpose and quasi-experimental in terms of method using pretest-posttest with a control group. The statistical population of this study consisted of all female high school students in Tehran in the academic year 2019-2020. First, a school was selected from among them and 30 students were selected by random sampling method and were randomly assigned to the experimental group (15 people) and the control group (15 people). The experimental group was trained in 8 sessions of the Mindfulness Training Program (2017). The self-regulatory questionnaire by Pintrich and DeGroot (1990) and the Perry et al.'s (2001) Conscious Academic Control Scale were used to collect data. One-way covariance test was used to analyze the data. The results showed that mindfulness training method has a significant effect on increasing students' self-regulation and conscious academic control.